Gender differences in library book borrowing volume: The influence of psychological variables and temporal moderation - Liu, Jiexuan (International Journal of Educational Technology and Learning, 2025)
This study explores gender differences in library book borrowing with psychological variables and temporal moderation. Using PCA, SEM, logistic regression, and 2SLS, it analyzes reading preferences and borrowing behaviors. Females dominate literature and social science borrowing, while males prefer military, transportation, and STEM materials. SEM shows moderate factor suitability (KMO: 0.683 for males, 0.659 for females), with distinct structures: males have a three-factor model, and females a two-factor model. Logistic regression reveals a temporal decline in total borrowing volume’s positive effect on renewal behavior, with significant volume-time interactions (p < 0.001). 2SLS confirms that predicted variables from time, psychological factors, and renewal behavior influence borrowing volume differently by gender. The findings highlight the complex interplay of gender, psychology, and time in library usage, guiding resource allocation and gender-specific services.